(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper is focus on the Refocusing Computer Engineering and Computer Sciences Education for Economic Sustainability and Local Input Contents of Computer and mobile phones in Nigeria. There is over ten millions computer system, and more than hundred millions mobile phones in use in Nigeria. All hardware, software and accessories of the computer systems/mobile phones components use in Nigeria are imported from foreign countries e.g. China, Taiwan, USA, Europe and Dubai in foreign currencies and when exchanged in Nigeria currency (naira). The foreign exchange trough the importation is of adverse to the country economy sustainability. Nigeria can improve her value added tax on locally made or assembled computer and mobile phones by fabricating some of the components and accessories from local raw materials. This could be achieved by refocusing and rebranding computer engineering and computer sciences education for students to acquire skills, and knowledge needed for industrial revolution and entrepreneurship for economic sustainability.